Enzyme immobilization on epoxy supports in reverse micellar media: prevention of enzyme denaturation - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Yalangi; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Journal of Molecular Catalysis B-Enzymatic, 2012)
Immobilization of enzymes such as alpha-chymotrypsin (EC 3.4.21.1), yeast alcohol dehydrogenase (YADH) from Saccharomyces cerevisiae (EC 1.1.1.1) and glucose dehydrogenase (GDH) from Gluconobacter cerinus (EC 1.1.1.119) has been carried out. Copolymers of allyl glycidyl ether (AGE) crosslinked with 25% ethylene glycol dimethacrylate (EGDM) (25 mg, dry wt) were contacted with the enzymes solubilized in reverse micellar media (0.5-5 mg/mL)(overall) of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) salt in isooctane, and cetyl trimethylammonium bromide (CTAB) in chloroform-isooctane (50:50, v/v). Although the enzymes are readily denatured (>90%) after adsorption on the copolymer in aqueous buffers, no such adsorption-induced denaturation takes place in reverse micelles. alpha-Chymotrypsin is remarkably stable in AOT reverse micelles when 0.025 M citrate buffer of pH 9.0 containing 2 mM CaCl2 is used in the water pools instead of Tris-HCl buffer of pH 8.5. It was possible to achieve enzyme concentration of 5 mg/mL in 0.3 M AOT at molar ratio of water to surfactant, (W-0), 30 and to obtain alpha-chymotrypsin loading of 20 mg/g of copolymer. The recovered enzyme solution can be reused with a fresh batch of polymer after supplementing the depleted solution. The immobilized enzyme exhibits excellent stability in aqueous buffers at room temperature and can be recycled several times. YADH is stable in both AOT and CTAB reverse micelles while GDH is stable only in CTAB reverse micelles containing 0.05 M Tris-HCI buffer of pH 8.5. Interestingly, the combination of YADH (2.5 mg/g) and GDH (0.5 mg/g) co-immobilized on the copolymer using CTAB-chloroform-isooctane system can be used for regeneration and recycle of NADPH at least 50 times as exemplified by complete reduction of a prochiral ketoester, ethyl 4-phenyl-2,4-dioxobutyrate (10 mM) to ethyl (R)-2-hydroxy-4-phenylbutyrate (HPB ester) using NADPH (0.2 mM). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: allyl glycidyl ether; alpha-Chymotrypsin; ethylene glycol dimethacrylate; Glucose dehydrogenase; Reverse micelles; Yeast alcohol dehydrogenase